2001
DOI: 10.1094/phyto.2001.91.11.1098
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of Metchnikowia pulcherrima Strains Against Blue Mold of Apple

Abstract: Eight strains of Metschnikowia pulcherrima isolated over a 4-year period from an unmanaged orchard and selected for their biocontrol activity against blue mold (caused by Penicillium expansum) of apples were characterized phenotypically, genetically, and for their biocontrol potential against blue mold on apples. All strains grew well and only differed slightly in their growth in nutrient yeast dextrose broth medium at 1 degrees C after 216 h, but large differences occurred at 0 degrees C, with strain T5-A2 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 43 publications
3
73
0
5
Order By: Relevance
“…This difference was very clear in their effects on the growth of the various strains of C. albicans. Differential antagonistic effects of M. pulcherrima strains on the Aspergillus and Penicillium species were reported previously (Janisiewicz et al, 2001;Bleve et al, 2006).…”
Section: Antagonistic Activities Of M Pulcherrima Strains On Bacterimentioning
confidence: 55%
“…This difference was very clear in their effects on the growth of the various strains of C. albicans. Differential antagonistic effects of M. pulcherrima strains on the Aspergillus and Penicillium species were reported previously (Janisiewicz et al, 2001;Bleve et al, 2006).…”
Section: Antagonistic Activities Of M Pulcherrima Strains On Bacterimentioning
confidence: 55%
“…Many yeast strains and other micro-organisms inhibiting plant pathogens have been reported, especially within the fruit-and vegetable-producing sector, and several new products have reached the commercial market (Janisiewicz & Korsten, 2002). The suggested modes of action of biocontrol yeasts are not likely to constitute any hazard for the consumer (Janisiewicz et al, 2001;Masih & Paul, 2002;Comitini et al, 2004;Santos & Marquina, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Many yeast strains and other micro-organisms inhibiting plant pathogens have been reported, especially within the fruit-and vegetable-producing sector, and several new products have reached the commercial market (Janisiewicz & Korsten, 2002). The suggested modes of action of biocontrol yeasts are not likely to constitute any hazard for the consumer (Janisiewicz et al, 2001;Masih & Paul, 2002;Comitini et al, 2004;Santos & Marquina, 2004a).The food and beverage industries were among the first to explore the application of killer-toxin-producing yeasts to kill spoilage micro-organisms (Lowes et al, 2000). Yeast strains often achieve competitive advantage by producing killer toxins, which kill off competing sensitive cells belonging to either the same or a different species (Young, 1987;Ciani & Fatichenti, 2001).…”
mentioning
confidence: 99%
“…Some authors have shown that the best antagonist against fungi that cause fruit decay is the very microfl ora from their surfaces (17)(18)(19). Our results confirm that microfl ora naturally occurring on fruit surfaces could provide effective protection against fungal growth and patulin accumulation.…”
Section: Apple Juicementioning
confidence: 99%